THE INFLUENCE OF BANKRUPTCY LAW IN THE SETTLEMENT OF PROBLEM DEBT LOANS RELATED TO INVESTMENT DEVELOPMENT IN INDONESIA: THE INFLUENCE OF BANKRUPTCY LAW IN THE SETTLEMENT OF PROBLEM DEBT LOANS RELATED TO INVESTMENT DEVELOPMENT IN INDONESIA - YUHELSON, YUHELSON (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This study aims to determine the extent of the influence of Bankruptcy law consisting of Bankruptcy statements and Suspension of Debt Payment Obligations (PKPU), as one of the legal instruments in the settlement of problem loans in Indonesia consisting of management, peace, and/or settlement/sale of debtor assets carried out by the Curator in the bankruptcy process, or the Administrator in the PKPU process. The Bankruptcy declaration mechanism is based on a court decision which results in the execution having the same legal force as a court decision in general, so that the execution of bankrupt debtor assets must be carried out through public sales/auctions so that transparent, accountable, and accountable sales can be carried out. Meanwhile, the PKPU mechanism is intended to achieve peace so that debtors' debts and problematic credits can be restructured to creditors and so that the debtor's business can run again. Bankruptcy legal instruments are now a trend in resolving debt disputes or bad credit that is most in demand because of its faster resolution, considering that Bankruptcy law has a fast-dimensional legal system (speedy trial), so that the rights of creditors and debtors can be more guaranteed based on applicable law. Both through the Bankruptcy declaration mechanism and PKPU, both are intended to protect the interests of debtors and creditors.